REKREATIVITAS LITERER DALAM NOVEL “DE JOURNAL” KARYA NANENG SETIASIH - Serly Tianasari; Susandi; Ari Nugrahani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines literary recreativity in the novel De Journal by Naneng Setiasih as reflected through narrative strategies, storytelling techniques, and the reconstruction of meaning, character experiences, and social discourse. The study aims to describe the forms of literary recreativity and explain how the novel reconstructs reality through aesthetic and interpretative processes. This research employed a qualitative descriptive method with an interpretative approach. The data source was the novel De Journal, while the data were collected through close reading and note-taking techniques. The data were analyzed using narrative and hermeneutic approaches through stages of reduction, classification, interpretation, and conclusion drawing. The results show that literary recreativity in the novel is manifested through six main aspects: spatial, cultural, subjective, temporal, symbolic, and ideological recreativity. These aspects are strengthened by the use of first-person narration, internal focalization, monologues, rhetorical questions, figurative language, and reflective narration. The novel not only represents reality but also reconstructs meaning critically through issues of gender, culture, environment, spirituality, and social life. Thus, literary recreativity in De Journal demonstrates that literary works function as aesthetic, reflective, and ideological spaces that encourage readers to reinterpret social reality and human experience.